Estimation of relationship between eating habits and body mass index of students in Mount Kenya University, Rwanda - Waweru, Wilson R.; Marete, Onesmus T. (International Journal Of Community Medicine And Public Health, 2017)
Background: Eating habits are a major concern among university students especially due to the transition from home environment where parents determine what to be eaten, to new environments where they or their peers choose the diet. Eating habits are considered determinants of health conditions and has been linked to death from Non-communicable diseases. Methods: This cross-sectional study was conducted in school of Health Sciences at Mount Kenya University. A total of 630 students from entire school of health science constituted the target population for the study. Sample size of 245 students was established. Stratified sampling technique was used to select students from department of Medical laboratory science, Nursing, Pharmacy and Public health who formed sample size for the study. Close-ended questionnaire was used as a tool for data collection. Results: The study found that majority of students had normal weight (65%) but there is a fairly high occurrence of overweight (20%) among the students. Further, female students skipped the three main meals i.e. breakfast, lunch and supper more frequently than male students. In addition, this study found that, the P-values of the chi-square test were greater than 0.05 hence there was not conclusive evidence of a statistical significant relationship between frequency of taking breakfast (P = 0.070), lunch (P = 0.167), or supper (P = 0.217) and body mass index of the students. Further the study found that food availability (61%), friends (6%), cost (1%) and accessibility of food (32%) were the factors that influenced students eating behaviors. The finding showed no statistical relationship between eating home cooked food (P = 0.114), eating self-cooked food (P = 0.056), frequency of taking sweet beverages per week (P = 0.567). However there was statistically significant relationship between frequency of taking fast food per week (P = 0.000), frequency of consuming snacks per week (P = 0.001), frequency of consuming vegetables per week (P = 0.000), frequency of consuming fruits per week (P = 0.033), frequency of consuming deep fried food per week (P = 0.026), frequency of consuming chicken per week (P = 0.008) and body mass index of the students. Additionally the study found out that students considered either the cost of food 29%, availability of food for purchase, 22%, favorite meals 15% or balanced diet when making food choices. A significant relationship between meals planning and BMI (P = 0.000) was realized as well as between living arrangement of the students and body mass index (P = 0.000). Conclusions: The study concluded that the frequency of taking breakfast, lunch and supper has no relationship with body mass index of the students. However, frequency of taking fast food, frequency of consuming snacks, frequency of consuming vegetables, frequency of consuming fruits, frequency of consuming deep fried food and frequency of consuming chicken per week is statistically related to body mass index of students. The study also concluded that meal planning and living arrangement relates with student’s body mass index significantly.